Assessment Practice of Special Need Students in Special Education Schools in Zamfara State, Nigeria - Adaramaja Sheu, Lukman; Abdullahi, Abubakar Hauwau (Papanda Publisher, 2025)
Assessment practices of special need students have been a concern in the educational system of most countries, especially in Nigeria. The aim of this study is to examine the assessment practice of special need students in special education Schools in Zamfara state, Nigeria. The Survey design was adopted for this study. The population of the study comprised all the 55 teachers (special educators) in the two (2) School for Special Education in Zamfara State, which include School for Special Education Gusau and School for Special Education Gummi. School for Special Education Gusau and School for Special Education Gummi have 37 and 18 teachers respectively. Purposive or judgmental sampling technique was used to select all the 55 teachers of special education schools in Zamfara state from whom, we could gain deep insights and understandings of assessment practices in special schools. The instrument used for data collection is a researcher designed questionnaire namely “Special Educators’ Assessment Practice Questionnaire (SEAPQ)”. The Data collected were analyzed using descriptive statistics of Weighted Mean and Standard Deviation. The results showed that the components of student assessment practice conducted among special need students are curriculum-based assessments, intelligence Quotient (IQ), Test screening test, academic achievements, developmental assessments and end-of-grade assessments, and the methods of assessment used are formative assessment, summative assessment, speech therapy evaluation/language scales, developmental scales, diagnostic assessment, standardized test and direct observation. The findings also revealed that special educators’ professional competence in choosing assessment methods appropriate for special need students, administering, scoring, and interpreting of their results and recognizing unethical and inappropriate assessment methods are inadequate. Based on these findings, it was recommended that Special educators should be train on all the components of assessments practices that will benefit special needs students learning outcomes.